2008
DOI: 10.1093/treephys/28.8.1269
|View full text |Cite
|
Sign up to set email alerts
|

Masting in Fagus crenata and its influence on the nitrogen content and dry mass of winter buds

Abstract: In Fagus, full-mast seeding years are invariably followed by at least one non-mast year. Both flower and leaf primordia develop during the summer within the same winter buds. Flower bud initiation occurs when the N content of developing seeds is increasing rapidly. We hypothesized that competition for nitrogen (N) between developing seeds and buds limits flower primordium formation in mast years and, hence, limits seed production in years following mast years. We tested this hypothesis in three Fagus crenata B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
63
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 32 publications
9
63
0
2
Order By: Relevance
“…Current-year leaves increased to the highest fraction of leaf dry mass 3 years after the masting. Singh et al (1990) and Han et al (2008) showed how masting influenced negatively the production of leaf primordia and growth in the following years. Leaf shedding is enhanced after the masting event.…”
Section: Discussionmentioning
confidence: 99%
“…Current-year leaves increased to the highest fraction of leaf dry mass 3 years after the masting. Singh et al (1990) and Han et al (2008) showed how masting influenced negatively the production of leaf primordia and growth in the following years. Leaf shedding is enhanced after the masting event.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a drastic reduction in crown cover was detected in two birch species (Betula alleghaniensis and B. papyrifera) during a mast year (Gross 1972), and Fagus sp. has also shown drastic reductions in crown conditions due to large seed harvests (Innes 1992;Ferretti et al 1998;Han et al 2008;Vicca et al 2014). In these kinds of forests, masting could be detected after substantial decreases in the EVI not explained by weather conditions .…”
Section: Rethinking the Influence Of Weather On Masting Behaviourmentioning
confidence: 99%
“…For example, competition for nitrogen (N) and carbohydrates between floral and leaf buds may drive variation in flowering in some species (Han et al 2008), and these competitive interactions may be relaxed through increasing soil nutrients (e.g., Neilsen et al 1990). High-fertility soils are thus predicted to increase reproductive output (i.e., seeds per m 2 ) and lower interannual variation, increasing the number of years with medium-or low-intensity flowering at the expense of those with negligible flowering (Kelly and Sork 2002).…”
Section: Introductionmentioning
confidence: 99%